The influence of point defects on the temperature dependence of quasi-two-dimensional 2H-NbSe₂ resistivity - Mamalui, A.A.; Shelest, T.N.; Fatyanova, N.B.; Sirenko, V.A. (Functional Materials, 2005)
The processes of point defects forming in quasi-two-dimensional 2H-NbSe₂ crystals were studied experimentally by measuring the temperature-time resistivity dependencies in the temperature range 300-500 K. It is found out that the special property of (selenium vacancies) formation is the dependence of their formation energy on the time of isothermal exposure, i.e. concentration.